APLIKASI HORMON ESTRADIOL UNTUK PENGENDALIAN KANIBALISME PADA BENIH LELE SANGKURIANG (Clarias gariepinus) PADA BUDI DAYA SKALA MASSAL - Nur Amaliah Putri; Deny Sapto Chondro Utomo; Evi Rahayuni; Catur Setiowibowo (Jurnal Akuakultur Rawa Indonesia, 2022)
African catfish (Clarias gariepinus) is a commodity admired by both farmers and consumers. However, one obstacle in nursery process, namely the high mortality of fry due to cannibalism, especially in mass scale nursery system. One alternative that can be done to reduce the potential for cannibalism is through a hormonal approach, namely the application of estradiol-17? hormone. This study aimed to evaluate the effect of estradiol-17? hormone within batch spawning groups on level of cannibalism of african catfish fry. This study used a non factorial randomized block design with three levels of estradiol-17? hormone doses treatment, i.e., estradiol-17? hormone on feed of 0 mg/kg feed, estradiol-17? hormone of 30 mg/kg feed, estradiol-17? hormone of 60 mg/kg feed, on three batch spawning groups. African catfish seeds were reared in concrete tanks with density of 1,194 fish/m2 within two weeks. The results showed that dose of estradiol-17? hormone treat-ment was not able to reduce cannibalism, but in third batch spawning group sup-ported absolute weight of 0.32 g (P<0.05), and in second batch spawning group were reduced cannibalism potential parameter by 0.61%, and a survival rate of 70.04%. Key words : Batch Spawning, Cannibalism, Clarias gariepinus, Estradiol-17?